2010
DOI: 10.1109/tuffc.2010.1676
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast crystallization kinetics in (Pb,La)(Zr0.30Ti0.70)O3 thin films by pulsed excimer laser annealing

Abstract: The crystallization kinetics of laser-annealed Lamodified Pb(Zr,Ti)O₃ (PLZT) thin films on LaNiO₃-coated silicon substrates were investigated for substrate temperatures below 400 °C. A KrF excimer laser having a ~20 ns pulse width and an energy density ~40 mJ/cm² was used to crystallize the films. The perovskite phase developed with cumulative laser pulse exposures; it was found that ~380 to 400 nm thick films could be fully crystallized for a total exposure time of 0.1 to 1 ms. Laser-crystallized films exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…[3][4][5] It also allows development of texture in Pb(Zr 0.52 Ti 0.48 )O 3 (PZT (52/48)) to achieve excellent piezoelectric properties. 6 However, limited thicknesses ($300 nm) can be crystallized in this manner due to the limited thermal diffusion length of the absorbed laser pulse in the film.…”
Section: Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] It also allows development of texture in Pb(Zr 0.52 Ti 0.48 )O 3 (PZT (52/48)) to achieve excellent piezoelectric properties. 6 However, limited thicknesses ($300 nm) can be crystallized in this manner due to the limited thermal diffusion length of the absorbed laser pulse in the film.…”
Section: Thin Filmsmentioning
confidence: 99%
“…6 However, limited thicknesses ($300 nm) can be crystallized in this manner due to the limited thermal diffusion length of the absorbed laser pulse in the film. 4 On the other hand, some PZT (52/48) thin film MEMS applications require thicknesses >1 lm.…”
Section: Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, direct integration of the piezoelectric thin film with a microchip would improve response times in sensors, potentially coupled with low‐cost manufacturing . Pulsed‐laser treatment is one way to selectively heat the film to achieve the high temperatures required for perovskite phase crystallization, while causing minimal heating of the underlying substrate …”
Section: Introductionmentioning
confidence: 99%
“…3 Pulsed-laser treatment is one way to selectively heat the film to achieve the high temperatures required for perovskite phase crystallization, while causing minimal heating of the underlying substrate. [4][5][6][7][8][9][10] Moreover, in situ heat treatment of oxide thin films during growth can also benefit from reduced crystallization temperatures compared to a postdeposition thermal processing. 11,12 It has been shown that crystallization of ferroelectric thin films can be achieved by simultaneous laser annealing during growth at substrate temperatures of ≤400°C.…”
Section: Introductionmentioning
confidence: 99%